2018
DOI: 10.4038/sljb.v3i1.17
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on effect of buddhist pirith chanting and pop music on the growth and yield performance in rice (<em>Oryza sativa</em> L.)

Abstract: Music influences the growth of plants through either promoting or restricting the growth of plants. The effects of Pirith chanting and pop music were focused in the present study. Seeds of Two (02) rice varieties (Bg300 and Kaluheenati) were subjected to dormancy break treatment, kept in a soundproof confined chamber and arranged in Completely Randomized Design (CRD) with two (02) replicates and 10 seeds per replicate. Seeds were allowed to germinate under the sound rhythms; pop music, Pirith chanting and sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…Different audio control technologies (electronic music, rock music, and classical music) have promoted the growth of lettuce, especially under the influence of electronic music, and the production of edible parts has increased significantly. This is similar to the results of some studies on rosemary plants [45][46][47][48].…”
Section: Effect Of Music On Plant Growthsupporting
confidence: 91%
“…Different audio control technologies (electronic music, rock music, and classical music) have promoted the growth of lettuce, especially under the influence of electronic music, and the production of edible parts has increased significantly. This is similar to the results of some studies on rosemary plants [45][46][47][48].…”
Section: Effect Of Music On Plant Growthsupporting
confidence: 91%
“…The results of this study are basically consistent with those of some researchers [6][7][8][9]12,13,[26][27][28][29][30][31][32]. For example, researchers have found that the melodic features (pitch histogram) of almost all traditional Chinese (five-tone) folk music conformed to a normal distribution, whose melodic beauty is entirely in line with the Chinese culture of the golden mean [33,34].…”
Section: Coupling Mechanism and Design Of Urban Ecological Planning A...supporting
confidence: 90%
“…Traditional ethnic music can positively affect the productivity and quality of plants. Many studies are heading in that direction: Javanese music has been applied to Chinese broccoli (Brassica alboglabra) plants [16], and Desmodyium girans (Telegraph plant) [17] and rice (Oryza sativa) [18] show better growth performance when exposed to Buddhist pirith chants.…”
Section: What Is "Sound"mentioning
confidence: 99%